Two candidate brown dwarf companions around core helium-burning stars - Schaffenroth, Veronika; Classen, Lew; Nagel, K.; Geier, S.; Koen, C.; Heber, Ulrich; Edelmann, Heinz (Astronomy & Astrophysics, 2014)
Hot subdwarf stars of spectral type B (sdBs) are evolved, core helium-burning objects. The formation of those objects is puzzling, because the progenitor star has to lose almost its entire hydrogen envelope in the red-giant phase. Binary interactions have been invoked, but single sdBs exist as well. We report the discovery of two close hot subdwarf binaries with small radial velocity amplitudes. Follow-up photometry revealed reflection effects originating from cool irradiated companions, but no eclipses. The lower mass limits for the companions of CPD-64°481 (0.048 M) and PHL 457 (0.027 M) are significantly below the stellar mass limit. Hence they could be brown dwarfs unless the inclination is unfavourable. Two very similar systems have already been reported. The probability that none of them is a brown dwarf is very small, 0.02%. Hence we provide further evidence that substellar companions with masses that low are able to eject a common envelope and form an sdB star. Furthermore, we find that the properties of the observed sample of hot subdwarfs in reflection effect binaries is consistent with a scenario where single sdBs can still be formed via common envelope events, but their low-mass substellar companions do not survive.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Brown dwarfs; Subdwarfs